Silicon Nitride, a Bioceramic for Bone Tissue Engineering: A Reinforced Cryogel System With Antibiofilm and Osteogenic Effects - Lee, Seunghun S.; Laganenka, Leanid; Du, Xiaoyu; Hardt, Wolf-Dietrich; Ferguson, Stephen J. (Frontiers in Bioengineering and Biotechnology, 2021)
Silicon nitride (SiN, [Si3N4]) is a promising bioceramic for use in a wide variety of orthopedic applications. Over the past decades, it has been mainly used in industrial applications, such as the space shuttle engines, but not in the medical field due to scarce data on the biological effects of SiN. More recently, it has been increasingly identified as an emerging material for dental and orthopaedic implant applications. Although a few reports about the antibacterial properties and osteoconductivity of SiN have been published to date, there have been limited studies of SiN-based scaffolds for bone tissue engineering. Here, we developed a silicon nitride reinforced gelatin/chitosan cryogel system (SiN-GC) by loading silicon nitride microparticles into a gelatin/chitosan cryogel (GC), with the aim to produce a biomimetic scaffold with antibiofilm and osteogenic properties. In this scaffold system, the GC component provides a hydrophilic and macroporous environment for cells, while the SiN component not only provides antibacterial properties and osteoconductivity, but also increases the mechanical stiffness of the scaffold. This provides enhanced mechanical support for the defect area and a better osteogenic environment. First, we analyzed the scaffold characteristics of SiN-GC with different SiN concentrations, followed by evaluation of apatite forming capacity in simulated body fluid and protein adsorption capacity. We further confirmed an antibiofilm effect of SiN-GC against Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus) as well as enhanced cell proliferation, mineralization and osteogenic gene upregulation for MC3T3-E1 pre-osteoblast cells. Finally, we developed a bioreactor to culture cell-laden scaffolds under cyclic compressive loading to mimic physiological conditions and were able to demonstrate improved mineralization and osteogenesis from SiN-GC. Overall, we confirmed the antibiofilm and osteogenic effect of a silicon nitride reinforced cryogel system and the results indicate that silicon nitride as a biomaterial system component has a promising potential to be developed further for bone tissue engineering applications.